PENGARUH KOMUNIKASI MEREK TERHADAP LOYALITAS MEREK MELALUI KEPERCAYAAN MEREK SEBAGAI PEMEDIASI (Survei pada Konsumen Kecap Lombok Gandaria Merah di Luwes Kestalan Surakarta) - Rika, Odysiusoctavia; Suddin, Alwi; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims to understand the significant influence between: (1) Brand Communication to Brand Loyalty, (2) Brand Communication to Brand Trust, (3) Brand Trust to Brand Loyalty, (4) Brand Communication to Brand Loyalty which mediated by Brand Trust in Lombok Kecaria Gandaria Merah consumers at Luwes Kestalan Surakarta. Sample In this study is Lombok Gandaria Merah consumers at Luwes Kestalan Surakarta as many as 100 people taken randomly. Data collection techniques were carried out using a questionnaire. The technical analysis used is linear regression, t test, F test, direct effect test, indirect effect test, coefficient determination test, path analysis, and sobel test. The results of this study are: (1) Brand Communication has a significant effect on Brand Loyalty, (2) Brand Communication has a significant effect on Brand Trust, (3) Brand Trust has a significant effect on Brand Loyalty, (4) Brand Trust significantly mediates the effect of Brand Communication on Brand Loyalty.